Theory of Ion-Atom Collisions for Stopping Power Calculations - Bailey, Jackson (Curtin University, 2018)
This thesis is devoted to calculations of stopping power in ion-atom and ion-molecule collisions. A single-centre convergent close-coupling method is used to calculate the stopping power of simple atoms and molecules, including the water molecule, for antiprotons. A two-centre convergent close-coupling method, which includes electron capture, is used to calculate the stopping power of hydrogen for protons. The results presented in this thesis can be used for radiation-dose simulations in hadron therapy.